2013
DOI: 10.1080/1068316x.2011.614244
|View full text |Cite
|
Sign up to set email alerts
|

Victim impact statements and crime heinousness: a test of the saturation hypothesis

Abstract: In Payne v. Tennessee (1991), it was argued that the harmful effects of a victim impact statement (VIS) during sentencing are diminished as the heinousness of the crime increases. We tested this hypothesis by giving 180 mock jurors a summary of a murder trial that varied the presence/absence of VIS along with the crime heinousness (more/less). Participants gave significantly harsher sentencing ratings when VIS was present than when it was absent, and crime heinousness also significantly affected sentencing rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Other studies have found more modest effects of VIS on sentencing (e.g., Myers, Godwin, Latter, & Winstanley, 2004;Myers, Roop, kalnen, & kehn, 2013). In instances in which sentencing judgments were not measured, researchers have found VIS significantly affects judgments that are relevant to sentencing.…”
Section: Vis Juror Judgments and The Effect Of Specific Emotionsmentioning
confidence: 99%
“…Other studies have found more modest effects of VIS on sentencing (e.g., Myers, Godwin, Latter, & Winstanley, 2004;Myers, Roop, kalnen, & kehn, 2013). In instances in which sentencing judgments were not measured, researchers have found VIS significantly affects judgments that are relevant to sentencing.…”
Section: Vis Juror Judgments and The Effect Of Specific Emotionsmentioning
confidence: 99%
“…7 If successful, this approach might secure greater public confidence without 6 While some argue that victim impact statements might influence juries to support harsher sentences (Myers et al, 2013), there is convincing evidence that sentencing does not become more punitive with victim impact statements (Roberts 2009). …”
mentioning
confidence: 99%